Inconsequential harmonization of Danish competition law - Niels Blomgren-Hansen; H.Peter Møllgaard (Copenhagen Business School (CBS), Department of Economics, 1999)
By replicating Articles 85 and 86 of the EC Treaty the Danish Competition Act (put in force January 1998) constituted a shift from the control principle to the prohibition principle. This is an important improvement from the point of view that regulatory legislation should be designed to give business economics incentives to act in a socially beneficial way, placing the burden of efficiency losses at the party who can avoid such losses at the least expected cost. The act now correctly makes businessses ex ante liable, but two equally important elements of an optimally designed antitrust legislation are missing: (1) The authority of the enforcing agency to impose administrative fines of a magnitude that makes the expected cost of infringements negative; (2) An appropriate organizational structure. With these two deficiencies the practical signifiance of the shift of principle is likely to be insignificant.
hdl:10398/7547
Keywords: K21; L40; 330; Competition law; Antitrust economics; Deterring incentives; Design of enforcing agency